Elemental analysis of archaeological ochre: method and possibilities of X-ray fluorescence spectroscopy (based on materials of Neolithic and Aeneolithic sites of the Middle Trans-Urals and Western Siberia) - Iudina E.A.; Tonkushina M.O.; Kulesh N.A.; Ostroushko A.A. (Вестник археологии, антропологии и этнографии, 2016)
The article is dedicated to methodological aspects of the elemental analysis (X-ray fluorescence spectroscopy) of a natural mineral pigment — ochre. We chose oxide ochre obtained from the Neolithic and Aeneolithic sites of the taiga zone of Western Siberia and the Middle Urals (the end of VI — III millennium BC) as a source base. The questions of selection and preparation of archaeological samples, and of interpretive capabilities of the chosen approach are discussed in the article.